Spawn production and isolation for Auricularia fuscosuccinea (Mont.) Henn. and Crepidotus palmarum traditionally used in Pauna (Boyaca, Colombia) - Niño F., Yeina Milena; Peña C., Ehidy Rocío; Henao, Luis Guillermo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2017)
Fungi extracted from their natural environment represent a source of food and are a part of the traditions and livelihood strategies of the people who use them. The domestication of this resource strengthens its ecological value, promotes sustainable use and favors the conservation of the environment. In Boyacá, species of fungi are traditionally used by rural communities. This study aimed to strengthen the traditional knowledge and initiate the process of domestication from isolation and spore production of Auricularia fuscosuccinea and Crepidotus palmarum, two mushrooms eaten by inhabitants of Monte and Pinal, in Pauna (Boyaca). We conducted workshops, interviews and visits to the oak forests with local experts to collect the fungi in an exchange of experiences of domestication. Four culture media and three types of cereal grain were evaluated for isolates and spore production. The best isolation conditions included the PDAE medium for A. fuscosuccinea and EME for C. palmarum, incubated at 25 and 22°C, respectively. As a result of the evaluation of medium cultures that favor the mycelial growth rate, in the case of A. fuscosuccinea, there were no significant differences (P>0.05) in the efficiency of the culture media. However, for C. palmarum at 25°C, the significance level (P≤0.05) indicated that the EM medium favored the growth rate. In spore production, A. fuscosuccinea in wheat grains incubated at 25°C and C. palmarum in barley grains at 22°C had high percentages of substrate invasion.